Zwischen Transformation und Abolitionismus (Velbrück Wissenschaft, 2026)
Even in enlightened liberal societies, punishment seems to be without any alternative. Yet the debate about alternatives to punishment and criminal law is as old as these institutions themselves. In recent years, a new social, legal, and sociological sensitivity to the issue has emerged, reigniting the debate.